Assessment of wheat yield when subject to various sources of nitrogen - Camponogara, Alexandre da Silveira; Oliveira, Gislayne Alves; Georgin, Jordana; Rosa, Ana Lúcia Denardin da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
This study aimed to evaluate the effects of applying different nitrogen sources in the states of booting and silking on yield components and the wheat crop productivity (Triticum aestivum L., Quartz - OR Seeds). The experiment was conducted in Frederico Westphalen-RS. The experimental design was a randomized complete block design, with eight treatments and four replications. The treatments consisted of combinations of different sources and forms of N application that follow: T1 - control (no N), T2 - Fertilization base + urea, T3 - Basic fertilization + ammonium nitrate, T4 - Fertilizing base + urea + foliar nitrogen, T5 - Basic fertilization + ammonium nitrate + foliar nitrogen, T6 - Basic fertilization + foliar nitrogen, T7 - Basic fertilization + urea + ammonium nitrate and T8 - Basic fertilization + ammonium nitrate + urea. The ammonium nitrate application associated with the supplemental foliar N resulted in an increase in grain yield of 51.5% over the control to the control. Other income components also obtained average with significant magnitudes verified by Duncan test at 5% error probability.